2022
DOI: 10.2174/1871530321666210809155147
|View full text |Cite
|
Sign up to set email alerts
|

Association between Increased Bcl-2, Fas and FasL Levels and Inflammation Extent in Labial Salivary Glands During Primary Sjögren's Syndrome

Abstract: Background: Primary Sjögren syndrome (pSS) is a chronic autoimmune disease characterized by epithelial atrophy, mononuclear infiltration in exocrine glands resulting in defective function of these glands. In pSS, atrophy of the epithelium is caused by an increased amount of apoptosis. Objective: The main aim of this study is to investigate the role of the apoptosis-related factors by studying Bcl-2, Fas and FasL expression in relation to the extent of inflammation as well as the effect of therapy on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Indeed, apoptosis of SGECs is considered an essential pathogenetic mechanism for SS development through the accumulation of apoptotic debris and autoantigen discharge, which can activate the immune response [15,40]. In accord with these findings, it has been recently reported that increased plasma levels of pro-apoptotic molecules, including Bcl2, Fas, and FasL, are associated with more severe inflammation status in SS patients than controls [41]. Moreover, overexpression of lysosome-associated membrane glycoprotein 3 (LAMP3)-a lysosomal protein playing a central role in antigen presentation and cell survival-in SS-derived MSGs has been associated with increased SGEC apoptosis and higher serum autoantibodies in SS patients [42].…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, apoptosis of SGECs is considered an essential pathogenetic mechanism for SS development through the accumulation of apoptotic debris and autoantigen discharge, which can activate the immune response [15,40]. In accord with these findings, it has been recently reported that increased plasma levels of pro-apoptotic molecules, including Bcl2, Fas, and FasL, are associated with more severe inflammation status in SS patients than controls [41]. Moreover, overexpression of lysosome-associated membrane glycoprotein 3 (LAMP3)-a lysosomal protein playing a central role in antigen presentation and cell survival-in SS-derived MSGs has been associated with increased SGEC apoptosis and higher serum autoantibodies in SS patients [42].…”
Section: Discussionmentioning
confidence: 84%
“…In patients with SS, plasma BCL2 is associated with the severity of inflammation, and significantly increased compared with healthy controls. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that NO is considered as a key signaling molecule in several physiological activities, however, like most other inflammatory mediators, excessive production of NO in response to inflammatory stimuli mediate cellular/tissue injury. 24 27 Importantly, NO is a crucial marker for oxidative stress and inflammation. 28 Our report revealed a high rise in NO levels, which can result in the production of peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%